Quranic Hypnotherapy: An Interdisciplinary Study of Neuroscience, Communication Psychology, and Spirituality for the Golden Indonesia Character Education - Wulan, Intan Cahya; Setiawati, Rini; Gesit Yudha (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2026)
Abstract This study examines Quranic Hypnotherapy as a transformative communication model in character education through an interdisciplinary approach integrating Quranic studies, communication psychology, persuasive communication, neuroscience, hypnotherapy, and education. The theoretical framework draws on communication psychology, persuasive communication theory (Hovland and the Elaboration Likelihood Model), intrapersonal communication, transcendental communication, and instructional communication. Quranic Hypnotherapy is conceptualized as a process of internalizing Quranic values through repeated recitation in a relaxed mental state (alpha brainwave condition), enabling Quranic messages to be optimally received by the subconscious mind. This process represents both transcendental communication between humans and God and intrapersonal communication that influences emotional regulation, self-motivation, and behavioral formation. This study employs a qualitative descriptive method, grounded in a literature review of reputable national and international academic sources. The findings indicate that Quranic Hypnotherapy contributes to reducing anxiety, lowering academic stress, improving concentration and learning motivation, and promoting positive character development. Therefore, Quranic Hypnotherapy constitutes a transformative communication model that can be operationalized within character education policy. Keywords: Character Education; Communication Psychology; Quranic Hypnotherapy; Persuasive Communication; Transcendental Communication. Abstrak Penelitian ini mengkaji Hipnoterapi Al-Qur'an sebagai model komunikasi transformatif dalam pendidikan karakter melalui pendekatan interdisipliner yang mengintegrasikan studi Al-Qur'an, psikologi komunikasi, komunikasi persuasif, ilmu saraf, hipnoterapi, dan pendidikan. Kerangka teoritis mengacu pada psikologi komunikasi, teori komunikasi persuasif (Hovland dan Model Kemungkinan Elaborasi), komunikasi intrapersonal, komunikasi transendental, dan komunikasi instruksional. Hipnoterapi Al-Qur'an dikonseptualisasikan sebagai proses internalisasi nilai-nilai Al-Qur'an melalui pembacaan berulang dalam keadaan mental yang rileks (gelombang otak alfa), memungkinkan pesan Al-Qur'an diterima secara optimal oleh pikiran bawah sadar. Proses ini mewakili komunikasi transendental antara manusia dan Tuhan dan komunikasi intrapersonal yang memengaruhi regulasi emosional, motivasi diri, dan pembentukan perilaku. Penelitian ini menggunakan metode deskriptif kualitatif berdasarkan tinjauan literatur dari sumber akademik nasional dan internasional yang bereputasi. Temuan ini menunjukkan bahwa Hipnoterapi Al-Qur'an berkontribusi untuk mengurangi kecemasan, mengurangi stres akademik, meningkatkan konsentrasi dan motivasi belajar, dan mendorong pengembangan karakter yang positif. Dengan demikian, Hipnoterapi Al-Qur'an merupakan model komunikasi transformatif yang dapat dioperasionalkan dalam kebijakan pendidikan karakter. Kata Kunci: Hipnoterapi Al-Qur’an; Komunikasi Persuasif; Komunikasi Transendental; Pendidikan Karakter; Psikologi Komunikasi.